Síntese e caracterização do carbeto de molibdênio nanoestruturado para fins catalíticos na reação de oxidação parcial do metano - Gomes, Kalyanne Keyly Pereira (2006)
The nanostructures materials are characterized to have particle size smaller than 100 nm and could reach 1 nm. Due to the extremely reduced dimensions of the grains, the properties of these materials are significantly modified relatively when compared with the conventional materials. In the present work was accomplished a study and characterization of the molybdenum carbide, seeking obtain it with particles size in the nanometers order and evaluate its potential as catalyst in the reaction of partial methane oxidation. The method used for obtaining the molybdenum carbide was starting from the precursor ammonium heptamolybdate of that was developed in split into two oven, in reactor of fixed bed, with at a heating rate of 5ºC/min, in a flow of methane and hydrogen whose flow was of 15L/h with 5% of methane for all of the samples. The studied temperatures were 350, 500, 600, 650, 660, 675 and 700ºC and were conducted for 0, 60, 120 and 180 minutes, and the percent amount and the crystallite size of the intermediate phases were determined by the Rietveld refinement method. The carbide obtained at 660ºC for 3 hours of reaction showed the best results, 24 nm. Certain the best synthesis condition, a passivating study was accomplished, in these conditions, to verify the stability of the carbide when exposed to the air. The molybdenum carbide was characterized by SEM, TEM, elemental analysis, ICP-AES, TG in atmosphere of hydrogen and TPR. Through the elemental analysis and ICP-AES the presence carbon load was verified. TG in atmosphere of hydrogen proved that is necessary the passivating of the molybdenum carbide, because occur oxidation in room temperature. The catalytic test was accomplished in the plant of Fischer-Tropsch of CTGAS, that is composed of a reactor of fixed bed. Already the catalytic test showed that the carbide presents activity for partial oxidation, but the operational conditions should be adjusted to improve the conversion